2016
DOI: 10.21053/ceo.2015.01368
|View full text |Cite
|
Sign up to set email alerts
|

Disability of Hearing Impairment Is Positively Associated With Urine Albumin/Creatinine Ratio in Korean Adults: The 2011–2012 Korea National Health and Nutrition Examination Survey

Abstract: Objectives.The aim of this study was to determine whether chronic kidney disease (CKD) is associated with hearing thresholds in the nationwide, large-scaled Korean population.Methods.This study analyzed the data of 9,798 subjects of 19 years and older (4,387 males and 5,411 females). Urine albumin-to-creatinine ratio (ACR) was measured from first-voided spot urine samples. The air-conduction hearing threshold was measured at 0.5, 1, 2, 3, 4, and 6 kHz and pure tone audiogram (PTA) average was calculated as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…There is a highly significant association between hearing impairment and speech (p= .000) this Means that hearing impairment will effect on speech production in adults with hearing Impairment. Literature also reveals the same results (p=.001) as presenting in current study, P, Muriel TN et, .al ( 2018) conducted a study to find out relationship in between hearing impairment and speech production they find out that normal hearing is vital for speech comprehension or normal production of speech sounds so they concluded that hearing impairment have negative consequences in the production of normal speech sound ,these two modalities are significantly associated to each other's [23] which is also mentioned in the presenting study .p-value is less than 0.05 this means that, there is a positive association(p=.011) between hearing impairment and excretion problems in adults with hearing impairments, this table shows that adults with increasing severity level of hearing disability will have more excretion problem then individual with mild degree of hearing loss .Literature also reveals the similar result as in a study of Kim ,YS , L et,. al [24] ,they concluded that severity of hearing loss in adults is positively associated(p=.002) with increase albumin in the urine so this means that these two are positively in relationship with each other's as presenting in the current study.…”
Section: Discussionsupporting
confidence: 80%
“…There is a highly significant association between hearing impairment and speech (p= .000) this Means that hearing impairment will effect on speech production in adults with hearing Impairment. Literature also reveals the same results (p=.001) as presenting in current study, P, Muriel TN et, .al ( 2018) conducted a study to find out relationship in between hearing impairment and speech production they find out that normal hearing is vital for speech comprehension or normal production of speech sounds so they concluded that hearing impairment have negative consequences in the production of normal speech sound ,these two modalities are significantly associated to each other's [23] which is also mentioned in the presenting study .p-value is less than 0.05 this means that, there is a positive association(p=.011) between hearing impairment and excretion problems in adults with hearing impairments, this table shows that adults with increasing severity level of hearing disability will have more excretion problem then individual with mild degree of hearing loss .Literature also reveals the similar result as in a study of Kim ,YS , L et,. al [24] ,they concluded that severity of hearing loss in adults is positively associated(p=.002) with increase albumin in the urine so this means that these two are positively in relationship with each other's as presenting in the current study.…”
Section: Discussionsupporting
confidence: 80%